The Nature of Essence in the View of Neosadrāie Philosophers Authors - Mahdi Safaei asl; Mohammad Broomand (آموزه‌‌های فلسفه اسلامي, 2023)
Despite agreement among Neosadrāie philosophers on the primacy of existence, they have provided different accounts of the existence of essence. Some view essence as an external entity, while others do not consider it to be external. The external realization of the essence has also been explained by a group with the causative mode and others with the conditional mode. Among the philosophers who do not consider essence to be external, some consider the truth of nature to be real and others virtual. The main issue of this article is the manner in which essence is realized in the external world, and in response to this question, it is shown that essence not only does not exist in the external world but also its reality outside is virtual as well. The article further critiques opposing views and proves the superiority of the proposed theory. This is a fundamental-analytical study using library-based research methods.